Effects of topography on dynamics and mass loss of lake-terminating glaciers in southern Patagonia - Masahiro Minowa; Marius Schaefer; Pedro Skvarca (Journal of Glaciology)
Calving glaciers are highly sensitive to bedrock geometry near their terminus. To understand the mechanisms controlling rapid calving glaciers’ mass loss, we measured the lake topography in front of four lake-terminating glaciers in the southern Patagonian icefield. Using remotely sensed surface elevation data, we calculated flotation height and surface slope and compared those with changes in ice-front position, surface speed and surface elevation. Rapid retreat accompanied by rapid flow acceleration and ice surface steepening was observed at Glaciar Upsala from 2008–2011, and at O'Higgins and Viedma glaciers from 2016–present. Surface lowering in the lower part of Glaciar Upsala reached 30 m a−1 and was 18 m a−1 and 12 m a−1 at O'Higgins and Viedma glaciers, respectively. Near- or super-buoyant conditions were observed prior to these events, leading to gradual flow acceleration due to low effective pressure and decoupling from the bed. The super-buoyant condition and gradual acceleration imply full-thickness buoyant calving, which causes the ice front to retreat from the shallow bedrock topography with substantial flow acceleration. We conclude that the buoyancy force plays an important role in the rapid mass loss of lake-terminating glaciers in southern Patagonia.